Solidworks student design kit
SolidWorks℗ʼ 2001 is mechanical design automation software that takes advantage of the familiar Microsoft℗ʼ Windows℗ʼ graphical user interface. This easy-to-learn tool makes it possible for mechanical designers to quickly sketch out ideas, experiment with features and dimensions, and produce models and detailed drawings.